c.1 - Dandekar, V.M. (Pune, 1971)
THIS study is concerned with the problem of poverty in India. It is a problem of low national income and its unequal distribution; of slow pace of development and inequitable distribution of the small gains of development. Before one discusses how to meet the threat this problem poses, one should know its dimensions and understand the process through which it seems to be deepening. We shall therefore begin with a brief review of the situation at the beginning of the six ties, that is, in 1960-61.
Keywords: Poverty